2020
DOI: 10.7554/elife.62238
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution of nontransitive fitness in yeast

Abstract: A common misconception is that evolution is a linear ‘march of progress’, where each organism along a line of descent is more fit than all those that came before it. Rejecting this misconception implies that evolution is nontransitive: a series of adaptive events will, on occasion, produce organisms that are less fit compared to a distant ancestor. Here we identify a nontransitive evolutionary sequence in a 1000-generation yeast evolution experiment. We show that nontransitivity arises due to adaptation in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…However, when using glycerol or ethanol as nonfermentative carbon sources, growth was resumed without a significant increase of biomass as observed with lactic acid/lactate (Figure 1C and Supplementary Materials Figure S1B). These results would indicate that in this case, we are not yet fixing adaptive mutations, as expected if a genotypic switch took place after the adaptive process [42][43][44][45][46][47][48][49]. But the increase of carrying capacity in the YPL adapted lines is also in agreement with an increase of TCA fluxes, as explained in [50].…”
Section: Lactic Acid As Non-fermentable Carbon Source Affects S Cerevisiae Growth Parameterssupporting
confidence: 64%
“…However, when using glycerol or ethanol as nonfermentative carbon sources, growth was resumed without a significant increase of biomass as observed with lactic acid/lactate (Figure 1C and Supplementary Materials Figure S1B). These results would indicate that in this case, we are not yet fixing adaptive mutations, as expected if a genotypic switch took place after the adaptive process [42][43][44][45][46][47][48][49]. But the increase of carrying capacity in the YPL adapted lines is also in agreement with an increase of TCA fluxes, as explained in [50].…”
Section: Lactic Acid As Non-fermentable Carbon Source Affects S Cerevisiae Growth Parameterssupporting
confidence: 64%
“…We also observed a population of the stronger antagonist with reduced killing activity, showing that the strength of the antagonistic interaction varied throughout the experiments and raising the interesting question of how such a mutant succeeded in outcompeting its ancestor which made more toxin. A recent study found that a strain infected with the K1 killer virus first lost the ability to produce the toxin, and later lost immunity to the K1 toxin during an evolutionary experiment which lasted for 1000 generations in well-mixed liquid cultures ( Buskirk et al, 2020 ). In that context, immunity to the toxin was lost once the killer toxin was not present in the medium anymore.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a population of the stronger antagonist with reduced killing activity, showing that the strength of the antagonistic interaction varied throughout the experiments and raising the interesting question of how such a mutant succeeded in outcompeting its ancestor which made more toxin. A recent study found that a strain infected with the K1 killer virus first lost the ability to produce the toxin, and later lost immunity to the K1 toxin during an evolutionary experiment which lasted for 1,000 generations in well-mixed liquid cultures (Buskirk, Rojes, & Land, 2020). In that context, immunity to the toxin was lost once the killer toxin was not present in the medium anymore.…”
Section: Discussionmentioning
confidence: 99%